Environmental & architectural phenomenology. Vol. 35, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2024)
This winter/spring issue provides four book reviews and three essays: Cognitive scientist Andrea Hiott reviews psychotherapist Iain McGilchrist’s The Matter with Things; Architect Susan Ingham reviews Lisa Heschong’s Visual Delight in Architecture; Anthropologist Jenny Quillien reviews architect Howard Davis’s edited collection of Early and Unpublished Writings of Christopher Alexander; EAP editor David Seamon reviews Christopher Alexander’s Production of Houses; Architect Howard Davis reports on a recent event celebrating Alexander’s Mexicali self-help housing experiment; Architect Gary Coates provides the new preface to his recently reprinted Resettling America, originally published in 1981; Philosopher Jeff Malpas offers remarks for a memoriam event devoted to the late Bob Mugerauer, a co-founder of EAP; Anthropologist Jenny Quillien introduces a phenomenological reformulation of the ideas of early-twentieth-century geographer and environmental determinist Ellen Churchill Semple.
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals